Commitment to social responsibility in a third sector organization: The case of alfazema flower - Rodrigues, M. C.; Rosa, L.; Sousa, M.; Gomes, C. M.; Campos, W.; Barbieri, L. (Social innovation and entrepreneurship in the fourth sector: Sustainable best-practices from across the world, 2021)
Corporate Social Responsibility is one of the most studied themes over the last decades, both at organizational and at academic levels. It has assumed a very relevant role in companies because the goal is to increase the quality of life of the employees, the organization as a whole, and the communities, improving the current socioeconomic scenarios. In the present chapter is carried out one analysis descriptive of practices of Responsibility Social Corporate (RSC) existing in the Association of Pensioners, Pensioners and Elderly Flower of Lavender, institution private of Solidarity Social the County of Sintra. Thus, the purpose of this work is to analyze the perception of the employees, in that it relates to their practice of Responsibility Social through the method of study of the case. In the theoretical review, the concept of IPSS is approached, the evolution of the concept of CSR, and some conceptual models observed in the academic literature are presented. Then, some public SR policies are identified. Preliminary results suggest that, in general, social solidarity institutions are engaging in their public policy strategies for Social Responsibility.